Using information and communication technology as a time management tool among school principals in the secondary stage - Saleem Khasawneh, Mohamad Ahmad (Journal of Infrastructure, Policy and Development, 2024)
The purpose of this study was to explore the relationship between using effective information and communication technology tools and time management skills in school administrations. The study aimed specifically to identify the presence of differences in the responses of school principals towards using technology in time management after isolating the variables of gender, years of experience, and educational level. This study utilized the analytical-descriptive method to achieve its objectives. The study instrument included a questionnaire with 45 items. The study sample consisted of 190 principals from different public schools in four emirates in the UAE (Dubai, Abu Dhabi, Sharjah, and Al-Ain). The principals were selected randomly by sending them an electronic questionnaire. The findings of the study revealed similarities in the responses of the school principals to the questionnaire on the role of information and communication technology in helping them achieve better time management.